A review of the nomenclature and identity of Cotyledon mucronata and C. undulata (Crassulaceae subfam. Cotyledonoideae), two names variously applied to undulate leaf-margined material generally included in the synonymy of different varieties of C. orbiculata, with C. mucronata reinstated at the rank of species - Smith, Gideon F.; Crouch, Neil R. (Phytotaxa, 2025)
As circumscribed at present, Cotyledon (Crassulaceae subfam. Cotyledonoideae) is a small genus of about two dozen species. For the species and infraspecific taxa recognised in Cotyledon, almost 100 names are available. This resulted from the naming, especially at the rank of species, of the extraordinary natural variability of at least some of the recognised Cotyledon taxa. In some of the Cotyledon species upheld at present, a range of taxa are treated at the rank of varietas. For example, in C. orbiculata, four varieties are recognised in addition to the autonymic one. Horticulturally popular undulate leaf-margined variants of C. orbiculata, as attributed at present, were described as C. mucronata by J-B.P.A. de M. de Lamarck in 1786 and later redescribed as C. undulata by A.H. Haworth in 1819, with, in the protologues of both these names, a plate (and only that plate) published by Johannes [Johan] Burman in 1738 being unambiguously cited. Yet, C. mucronata was most recently placed in the synonymy of the autonymic C. orbiculata var. orbiculata and C. undulata in the synonymy of C. orbiculata var. oblonga. In this paper the nomenclature and taxonomy associated with these two names are revisited and clarified. We show that the two names, i.e., C. mucronata and C. undulata, are homotypic and that the name C. undulata is illegitimate and nomenclaturally superfluous. If the undulate-leaf margined variant of the broadly defined C. orbiculata is recognised at the rank of species—a view we implement here—the name to adopt is C. mucronata. The name C. undulata belongs in the synonymy of C. mucronata.